Revision of subgeneric system and species groups of Cephennodes Reitter, with redescriptions of problematic species (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2026)
The subgeneric division and species groups of the large genus Cephennodes Reitter, 1884 are revised. Aculeodes Jałoszyński & Nomura, 2009, syn. n. is placed as a junior synonym of Cephennodes s. str., thus reducing the number of subgenera to two. Cephennodes miharu Hoshina, 2021, syn. n. is placed as a junior synonym of C. kotori Hoshina, 2021; C. mizunoi Hoshina & Kishimoto, 2004, syn. n. as a junior synonym of C. vafer Kurbatov, 1995; C. brachyclavatides Jałoszyński, nom. n. is proposed as a replacement name for C. brachyclavatus Jałoszyński, 2025, preoccupied by C. brachyclavatus Jałoszyński, 2017. The following species are redescribed (some partly, to supplement existing data with new details) and assigned to subgenus or/and a species group: C. (s. str.) tuniseus (Pic, 1901); C. (s. str.) kotori Hoshina, 2021; C. (s. str.) moderatus (Kurbatov, 1995); C. (s. str.) akane Hoshina, 2020; C. (s. str.) maya Hoshina, 2021; C. (s. str.) yume Hoshina, 2017; C. (s. str.) yonaguniensis Hoshina, 2012; C. (s. str.) vafer Kurbatov, 1995; and C. (Fusionodes) otome Hoshina, 2016. Cephennodes tertius Jałoszyński, 2011 and C. leonensis Castellini, 2010 are placed in the nominotypical subgenus, and C. besucheti (Kurbatov, 1995) in the subgenus Fusionodes Jałoszyński, 2007. Cephennodes (s. str.) nanaka Hoshina, 2019 is discussed as a possible junior synonym of C. moderatus, and four species, C. koko Hoshina, 2021, C. nemu Hoshina, 2021, C. otome Hoshina, 2016, and C. sakura Hoshina, 2021 as probably identical with C. loebli (Kurbatov, 1995), all pending further study. Cephennodes s. str. is divided into twenty-two species groups, and the subgenus Fusionodes into six groups: Cephennodes (s. str.) araiorum group (5 spp.), bagongsilangensis group (2 spp.), bos group (8 spp.), cavifrons group (2 spp.), excavatus group (50 spp.), gokarnaensis group (3 spp.), impressifrons group (19 spp.), inflatipes group (4 spp.), latus group (2 spp.), leai group (3 spp.), lustricollis group (5 spp.), mahisapala group (2 spp.), obesus group (4 spp.), oblongopunctatus group (12 spp.), palpalis group (3 spp.), simonis group (21 spp.), simplicipes group (18 spp.), spatulipes group (14 spp.), sulcatus group (3 spp.), taurus group (14 spp.), tuberculifrons group (10 spp.), yunnanensis group (2 spp.), and Cephennodes (Fusionodes) graeseri group (9 spp.), hippopotamus group (9 spp.), loebli group (7 spp.), longilinguis group (4 spp.), microphthalmus group (6 spp.), and serratus group (2 spp.). Keys are given to identify species groups of Cephennodes (s. str.) and the subgenus Fusionodes.